PENGARUH KINERJA LINGKUNGAN, LEVERAGE, DAN PROFITABILITAS TERHADAP PENGUNGKAPAN EMISI KARBON - Erik Juan Kaesang; Hermi Hermi (STMIK Widuri Jakarta, 2025)
The increase in global carbon emissions has become a critical issue that demands transparency in corporate reporting, particularly in the energy sector, which is a significant contributor to climate change. This study aims to analyze the influence of environmental performance, leverage, and profitability on carbon emissions disclosure in energy sector companies. The research method uses a quantitative approach with secondary data from 20 energy sector companies listed on the Indonesia Stock Exchange for the period 2021-2023, resulting in 60 observations. Data analysis techniques use panel data regression with a Fixed Effect Model via EViews 12 software. Carbon emissions disclosure is measured using the Carbon Emission Disclosure Checklist (CEDC), environmental performance is proxied through the PROPER ranking, leverage is measured using the debt-to-asset ratio, and profitability is measured using the return-on-asset ratio. The results of the study indicate that environmental performance has a significant positive effect on carbon emission disclosure (p=0.0000), while leverage (p=0.9668) and profitability (p=0.9942) do not have a significant effect. Simultaneously, the three variables explain 96.2% of the variation in carbon emissions disclosure. The study's conclusion confirms that companies with superior environmental performance tend to be more transparent in disclosing carbon emissions information to maintain social legitimacy, while financial factors do not determine disclosure.